Microbial Oxidation of Arsenite: Regulation, Chemotaxis, Phosphate Metabolism and Energy Generation - Shi, Kaixiang; Wang, Qian; Wang, Gejiao (Frontiers in Microbiology, 2020)
Arsenic (As) is a metalloid that occurs widely in the environment. The biological oxidation of arsenite [As(III)] to arsenate [As(V)] is considered a strategy to reduce arsenic toxicity and provide energy. In recent years, research interests in microbial As(III) oxidation have been growing, and related new achievements have been revealed. This review focuses on the highlighting of the novel regulatory mechanisms of bacterial As(III) oxidation, the physiological relevance of different arsenic sensing systems and functional relationship between microbial As(III) oxidation and those of chemotaxis, phosphate uptake, carbon metabolism and energy generation. The implication to environmental bioremediation applications of As(III)-oxidizing strains, the knowledge gaps and perspectives are also discussed.